Study on failure of a new bridge over Sg. Kerawang, Pulai Chondong, Kelantan - 450501 Nik Ab. Hadi Hassan (Skudai : Universiti Teknologi Malaysia, 2003)
Thesis (Master of Engineering (Civil)) - Universiti Teknologi Malaysia, 2003